Outcome of Elective Surgery in Patients with Controlled Diabetes versus Non-Diabetic Patients - Tariq, Syed Hassan; Sheikh, Irfan Ali; Asif, Muhammad; Masud, Maheen; Tariq, Syeda Zainab; Masud, Abdullah Bin (Pakistan Armed Forces Medical Journal, 2025)
Objective: To assess the outcome of elective surgery in patients with controlled type II diabetes versus patients without any diabetes Study Design: Prospective Comparative Study. Place and Duration of Study: Combined Military Hospital, Rawalpindi Pakistan, Mar 2020 to May 2021. Methodology: A prospective study was conducted on 400 patients undergoing elective surgery at surgical unit of combined military hospital Rawalpindi during the study period. They were divided into two groups. One with controlled type II diabetes mellitus and other without type II diabetes mellitus. Patients were followed up for one month to look for the complications. Presence of surgical site infections, seroma formation, abscess formation and wound dehiscence were compared in both the groups. Results: A total of 400 patients who met the criteria for this study underwent elective surgeries during the study period. Mean age of patients who underwent the surgery 39.93±8.455 years. Out of 400, 296(74%) were male while 104(26%) were female. 261(65.25%) had no diabetes while 139(34.75%) had controlled diabetes. Abscess formation and wound dehiscence were the complications found statistically significantly more among the patients who had controlled diabetes mellitus as compared to those not having diabetes mellitus (p-value<0.05). Conclusion: Patients undergoing elective surgery though did not have much serious complications but still the patients having diabetes mellitus even well controlled at the time of surgery were more at risk of post-surgical complications like abscess formation and wound dehiscence.